Global adjustment and the future of Asian-Pacific economy : - Shinohara , Miyohei (Asian and Pacific Development Centre,Institute of Developing Economies, 1989)
Global adjustment and the role of Japan in the future of Asian - Pacific economy; Towards the Asian - Pacific age; Impacts of gobal adjustment on the Asian-Pacific economy; Trade and economic cooperation in the Asian-Pacific region.